Adolescent Menstrual Health: Profoundness of The Problem and The Rationale Behind Denial of Treatment - Smitha MC; Narayana Murthy MR; Srinivas BM; Renuka M (Medsci Publications, 2016)
Introduction: Menstrual health problems among adolescent girls is one of the major adolescent health issues and is also associated with anxiety. Discussing about such issues is considered to be ta- boo even among the family members which further aggravates the problem as they do not take treatment for the same. Hence to de- termine the prevalence of menstrual health problems among ado- lescent girls and to determine the help seeking practices and socio- demographic factors influencing the same this study was under- taken. Methods: Cross-sectional study was conducted among adolescent girl of 16 - 19 years. Data was collected by administering ques- tionnaire to the sample of 700 adolescents. Proportions, Chi - square analysis, Independent test and Binary logistic regression using SPSS V.22 was done. Results: 72% of the adolescent girls had one or other symptoms of menstrual problems. Of them 60.2% sought help for their problems with majority consulting family members, followed by Doctors. Among those who did not seek help, perceiving that the problem to be less severe was the commonest reason given. Conclusion: Age, presence of siblings, birth order and type of fam- ily were significant independent predictors of help seeking behavior.